An open-label, multicenter, randomized, crossover study comparing sildenafil citrate and tadalafil for treating erectile dysfunction in Chinese men naïve to phosphodiesterase 5 inhibitor therapy - Bai, Wen-Jun; Li, Hong-Jun; Dai, Yu-Tian; He, Xue-You; Huang, Yi-Ran; Liu, Ji-Hong; Sorsaburu, Sebastian; Ji, Chen; Jin, Jian-Jun; Wang, Xiao-Feng (Asian journal of andrology, 2015)
The study was to compare treatment preference, efficacy, and tolerability of sildenafil citrate (sildenafil) and tadalafil for treating erectile dysfunction (ED) in Chinese men naοve to phosphodiesterase 5 (PDE5) inhibitor therapies. This multicenter, randomized, open-label, crossover study evaluated whether Chinese men with ED preferred 20-mg tadalafil or 100-mg sildenafil. After a 4 weeks baseline assessment, 383 eligible patients were randomized to sequential 20-mg tadalafil per 100-mg sildenafil or vice versa for 8 weeks respectively and then chose which treatment they preferred to take during the 8 weeks extension. Primary efficacy was measured by Question 1 of the PDE5 Inhibitor Treatment Preference Questionnaire (PITPQ). Secondary efficacy was analyzed by PITPQ Question 2, the International Index of Erectile Function (IIEF) erectile function (EF) domain, sexual encounter profile (SEP) Questions 2 and 3, and the Drug Attributes Questionnaire. Three hundred and fifty men (91%) completed the randomized treatment phase. Two hundred and forty-two per 350 (69.1%) patients preferred 20-mg tadalafil, and 108/350 (30.9%) preferred 100-mg sildenafil (P < 0.001) as their treatment in the 8 weeks extension. Ninety-two per 242 (38%) patients strongly preferred tadalafil and 37/108 (34.3%) strongly the preferred sildenafil. The SEP2 (penetration), SEP3 (successful intercourse), and IIEF-EF domain scores were improved in both tadalafil and sildenafil treatment groups. For patients who preferred tadalafil, getting an erection long after taking the medication was the most reported reason for tadalafil preference. The only treatment-emergent adverse event reported by > 2% of men was headache. After tadalafil and sildenafil treatments, more Chinese men with ED naοve to PDE5 inhibitor preferred tadalafil. Both sildenafil and tadalafil treatments were effective and safe.